5 nm Silver Nanoparticles Amplify Clinical Features of Atopic Dermatitis in Mice by Activating Mast Cells. Issue 9 (22nd December 2016) - Kang, HanGoo; Kim, Seungjae; Lee, Kwang Hoon; Jin, Shan; Kim, Seo Hyeong; Lee, Kangtaek; Jeon, Hyungjoon; Song, Young‐Geon; Lee, Sang‐Won; Seo, Jinwon; Park, Soomin; Choi, In‐Hong
Abstract : The triggering effect of silver nanoparticles (NPs) on the induction of allergic reactions is evaluated, by studying the activation of mast cells and the clinical features of atopic dermatitis in a mouse model. Granule release is induced in RBL‐2H3 mast cells by 5 nm, but not 100 nm silver NPs. Increases in the levels of reactive oxygen species (hydrogen peroxide and mitochondrial superoxide) and intracellular Ca ++ in mast cells are induced by 5 nm silver NPs. In a mouse model of atopic dermatitis induced by a mite allergen, the skin lesions are more severe and appear earlier in mice treated simultaneously with 5 nm silver NPs and allergen compared with mice treated with allergen alone or 100 nm silver NPs and allergen. The histological findings reveal that number of tryptase‐positive mast cells and total IgE levels in the serum increase in mice treated with 5 nm silver NPs and allergen. The results in this study indicate that cotreatment with 5 nm silver NPs stimulates mast cell degranulation and induces earlier and more severe clinical alterations in allergy‐prone individuals. Abstract : 5 nm silver nanoparticles (NPs) at a low level can amplify allergic symptoms. Granule release and reactive oxygen species generation are induced in mast cells in vitro. In a mouse model of atopic dermatitis, skin lesions are more severe and appear earlier with cotreatment of 5 nm silver NPs and allergen, which are supported by increased serum IgE levels and activated mast cells in skin.